Antiaging effects of dietary supplements and natural products - Gao, Lulu; Liu, Xudong; Luo, Xiaoyan; Lou, Xiaofan; Li, Pusen; Li, Xian; Liu, Xiaomeng (Frontiers in Pharmacology, 2023)
Aging is an inevitable process influenced by genetics, lifestyles, and environments. With the rapid social and economic development in recent decades, the proportion of the elderly has increased rapidly worldwide, and many aging-related diseases have shown an upward trend, including nervous system diseases, cardiovascular diseases, metabolic diseases, and cancer. The rising burden of aging-related diseases has become an urgent global health challenge and requires immediate attention and solutions. Natural products have been used for a long time to treat various human diseases. The primary cellular pathways that mediate the longevity-extending effects of natural products involve nutrient-sensing pathways. Among them, the sirtuin, AMP-activated protein kinase, mammalian target of rapamycin, p53, and insulin/insulin-like growth factor-1 signaling pathways are most widely studied. Several studies have reviewed the effects of individual natural compounds on aging and aging-related diseases along with the underlying mechanisms. Natural products from food sources, such as polyphenols, saponins, alkaloids, and polysaccharides, are classified as antiaging compounds that promote health and prolong life via various mechanisms. In this article, we have reviewed several recently identified natural products with potential antiaging properties and have highlighted their cellular and molecular mechanisms. The discovery and use of dietary supplements and natural products that can prevent and treat multiple aging-related diseases in humans will be beneficial. Thus, this review provides theoretical background for existing dietary supplements and natural products as potential antiaging agents.